Nutrients, buffer capacity, iminoacids and phenolic compounds as chemical parameters to indicate fire damages in Pinus pinaster trees - Alonso, M.; Rozados, M. J.; Vega, J. A.; Bara, S.; Cuiñas, P. (Forest Systems, 1998)
Changes in the level of some chemical parameters are researched in needles, juvenile needles and roots of P. pinaster trees caused by fire impact of three fire front linear intensities: 146 Kw.m-1 (QII), 357 (QI), and 423 (QIII) Kw.m-1, in Pontevedra, Galicia, NW of Spain. The most important variations are observed in needles. The free protocatechuic acid is a very sensitive parameter; it decreases to 48 p. 100 in QII, 40 p. 100 in QI and 68 p. 100 in QIII in relation to the control plot. Other good indicator is the free p-hidroxybenzoic acid, that falls in QII andQI to 61 p. 100 and 78 p. 100 respectively, and increases to 96% in the most intensity burned plot, QIII. The phosphorus level decreases in QII and QIII a 26 and 47 p. 100 respectively. The highest intensity fire (QIII) induces changes in a lot of parameters, other different from those in needles. The values of potassium, zinc and buffer capacity decrease and the values of calcium, copper, iron, astringency, total polyphenols, condensed tannins, free L-proline, free gallic acid, esterified protocatechuic and syringic acid increase. In roots, zinc is a good indicator. It descends in all cases researched. The level of total polyphenols falls in QII and QIII and free protocatechuic acid increases in QIII. In juvenile needles, except buffer capacity that decreases in QIII, we do not observe significative changes in other parameters.